Developing Social Engineering to Improve Social Awareness of Children's Education based on Local Knowledge - Helmuth Y. Bunu, Yunike Wati, Endang Purwaningsih (International Journal of Advanced Science and Technology, 2020)
This research aimed to develop a social awareness improvement model on children based on local knowledge. The study approach was model development according to previous study covering theory, social needs assessment, data collection, and analysis method. The designed model in this study will be furtherly used to improve children’s social awareness through study groups, parental socialization of children’s education, study time determination, parental accompaniment, and regular teacher visitation. Formation of study group, socialization of educational values to parents, study time arrangement, parental accompaniment training, and teacher study in the developed model can increased the community awareness of the education importance in Pahandut Village.